The use of a raindrop aggregate destruction device to evaluate sediment and soil organic carbon transport - L. Xiao; Y. Hu; P. Greenwood; N. J. Kuhn (Geographica Helvetica, 2015)
Raindrop impact and subsequent aggregate breakdown can potentially change the movement behaviour of soil fractions and thus alter their transport distances when compared against non-impacted aggregates. In a given water layer, the transport distances of eroded soil fractions, and thus that of the associated substances across landscapes, such as soil organic carbon (SOC) and phosphorous, are determined by the settling velocities of the eroded soil fractions. However, using mineral size distribution to represent the settling velocities of soil fractions, as often applied in current erosion models, would ignore the potential influence of aggregation on the settling behaviour of soil fractions. The destructive effects of raindrops impacting onto aggregates are also often neglected in current soil erosion models. Therefore, the objective of this study is to develop a proxy method to effectively simulate aggregate breakdown under raindrop impact, and further identify the settling velocity of eroded sediment and the associated SOC. Two agricultural soils with different sandy and silty loam textures were subjected to rainfall using a raindrop aggregate destruction device (RADD). The aggregates sustained after raindrop impact were fractionated by a settling tube into six different classes according to their respective settling velocities. The same mass amount of bulk soil of each soil type was also dispersed and sieved into the same six classes, to form a comparison in size distribution. The SOC content was measured for each settled and dispersed class. Our results show the following: (1) for an aggregated soil, applying dispersed mineral grain size distribution, rather than its actual aggregate distribution, to soil erosion models would lead to a biased estimation on the redistribution of eroded sediment and SOC; (2) the RADD designed in this study effectively captures the effects of raindrop impact on aggregate destruction and is thus able to simulate the quasi-natural sediment spatial redistribution; (3) further RADD tests with more soils under standard rainfall combined with local rainfalls are required to optimize the method.